A proteomic study of the effect of UV-B on the regulatory mechanism of flavonoids metabolism in pea seedlings - Fu, Xin; Xu, Yinghao; Lu, Ming (Frontiers in Nutrition, 2023)
This study aimed to investigate the mechanism of response of pea seedlings to UV-B stress from a proteomic perspective. In this experiment, we measured the growth of pea seedlings in two groups affected by UV-B and unaffected by UV-B and conducted proteomic analysis. The results showed that the ascorbic acid content of UV-B-irradiated pea seedlings increased by 19.0%; the relative content of flavonoids increased by 112.4%; the length of edible parts decreased by 14.2%, and the elongation of roots increased by 11.4%. Proteomics studies showed a significant increase in the levels of CHI, F3'5'H, F3H, F3'H, C4H, and CHR, which are key enzymes for flavonoid synthesis. RT-qPCR indicated that the expression of the regulatory genes of these enzymes was significantly upregulated. This study provided a basis for further studies on the flavonoid response mechanism in pea seedlings during UV stress.